Local Culture as an Effort to Strengthen Community’s Social Solidarity Value - Listyawati, Andayani (Jurnal Penelitian Kesejahteraan Sosial, 2018)
Local culture has been meant as local value produced by community in given territory that has been formed naturally, got through educational process from time to time and generation to generation. Culture that mentioned above is tradition, law, thinking pattern, and art. The implementation of culture in community contains social solidarity value because they were done involving community members interaction. The existence of local culture hoped to support social solidarity value as then social resilience. Those motivating this study that presented through descriptive approach. Through interview, observation, and documentary analysis, it can be described that Banjar Regency, South Kalimantan Province community, are still practising local culture through participation of all members of the community.